Discrete Traits of the Sternum and Ribs: A Useful Contribution to Identification in Forensic Anthropology and Medicine. Issue 3 (28th March 2013) - Verna, Emeline; Piercecchi‐Marti, Marie‐Dominique; Chaumoitre, Kathia; Bartoli, Christophe; Leonetti, Georges; Adalian, Pascal
Abstract During forensic anthropological investigation, biological profile is determined by age, sex, ancestry, and stature. However, several individuals may share the same profile. Observation of discrete traits can yield useful information and contribute to identification. This research establishes the frequency of discrete traits of the sternum and ribs in a modern population in southern France, using 500 computer tomography (CT) scans of individuals aged 15–60 years. Only discrete traits with a frequency lower than 10% according to the literature were considered, a total of eight traits. All scans examined were three‐dimensional (3D) volume renderings from DICOM images. In our population, the frequency of all the discrete traits was lower than 5%. None were associated with sex or age, with the exception of a single trait, the end of the xiphoid process. Our findings can usefully be applied for identification purposes in forensic anthropology and medicine.